Super-soft solvent-free bottlebrush elastomers for touch sensing. Issue 1 (23rd August 2019) - Reynolds, Veronica G.; Mukherjee, Sanjoy; Xie, Renxuan; Levi, Adam E.; Atassi, Amalie; Uchiyama, Takumi; Wang, Hengbin; Chabinyc, Michael L.; Bates, Christopher M.
Abstract : High sensitivity capacitive pressure sensors can be created with bottlebrush dielectric layers that overcome the limitations of traditional polymeric materials. Abstract : The sensitivity of capacitive pressure sensors is primarily determined by the modulus of a soft dielectric layer that reversibly deforms to produce an electrical signal. Unfortunately, the mechanical properties of conventional linear networks are constrained such that a lower limit on softness translates to poor capacitive pressure sensor performance. Here, we overcome this paradigm by leveraging the intrinsic "super-soft" characteristic of bottlebrush polymers. A simple light-induced crosslinking strategy is introduced to facilitate device fabrication and parallel plate capacitive pressure sensors constructed with these bottlebrush polymer networks exhibit up to a 53× increase in sensitivity compared to traditional material formulations, e.g., Sylgard 184. This combination of contemporary synthetic chemistry and application-driven materials design accentuates the opportunities available at the intersection of science and engineering.